GenomeAsia100K: Singapore Builds National Science with Asian DNA. Issue 2 (3rd April 2021) - Vimal, Manoj; Devi, Wairokpam Premi; McGonigle, Ian
Abstract: Most large population-based genomic studies have, until now, mainly focused on European ancestral populations. The Singapore-based GenomeAsia100K (GA100K) Consortium aims to address this bias by targeting major Asian populations and generating reference genomes for various ethnic groups. GA100K is also studying historical population migrations and providing bioinformatic tools that may help tackle diseases among Asia's multi-ethnic populations. These project goals transcend national boundaries, national genome projects, localized national science, and medicine. Rather, GA100K leverages the strategic location of Singapore as a regional nexus to advance science and technology within Singapore. GA100K is thus symptomatic of the Singaporean nation-state's ambition to be a knowledge-based economy and a regional biomedical hub. This article thus speaks to literature in STS that deals with the interface and entanglements of human tissue biobanks, human genome projects, and national development.